Use of Medicinal Plants in the Treatment of Erysipelas: A Review - Silva, Ivanise Brito da; Sá, Rafaela Damasceno; Macêdo, Danielle Patrícia Cerqueira; Randau, Karina Perrelli (Pharmacognosy Reviews)
Erysipelas infection is caused by Gram‑positive bacteria, in particular, β‑hemolytic Streptococcus pyogenes streptococci (B, C, and G). Typically treated with benzathine penicillin, the bacterial resistance and entry points in the skin favor disease recurrence. The use of herbs is a widespread traditional practice in the general population as an alternative method for curing diseases and symptoms with subsequent improvement in quality of life. It represents a more affordable treatment for the lower‑class population. This article reviews the use of medicinal plants in the treatment of erysipelas. A review was conducted identifying medicinal plants that can be used for the treatment of erysipelas. The search was conducted from publications from 1980 to 2016 by combining the search terms “medicinal plant” and “erysipelas.” The databases used in the research were PubMed, Web of Science, Google Scholar, Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Health Sciences, Cochrane Library, Scopus, and ScienceDirect. Data from the included articles are summarized in two tables with ethnopharmacological and pharmacological information. In this review, 30 articles were included. The selected plants have different popular indications of use, for example, to combat fever, inflammatory processes, and skin problems. The pharmacological studies evaluate the anti‑inflammatory, antimicrobial, antioxidant, toxicological, immunomodulatory, and antiprotozoal properties of plants using in vitro and in vivo methods. The plants mentioned in this study are reported as viable possibilities for the treatment of erysipelas. Future research may be carried out to elucidate the active principles, mechanisms of action, and pharmacodynamic aspects and thus propose a new treatment.
Keywords: Erysipelas; ethnopharmacology; medicinal plants; treatment